Book Review: Letta, Corrado G. M. (2008). Malaysia-Europe: Strategic Partnership for the Pacific Century. Malaysia, Putrajaya: Ministry of Foreign Affairs. - Wolf, Hans Volker (AEI Insights, 2021)
Revisiting Corrado Letta’s book on Europe and Malaysia (2008) is meant to re-introduce a unique ‘classic’ to a young audience in the area of education. Malaysia’s international role has grown in profile, since the book was first published and the international role and responsibility of the European Union have been exposed to big challenges. The recent integration of European Studies within language and communication programs at The Faculty of Languages and Linguistics, at The University of Malaya, and The Faculty of Modern Languages and Communication, at The Universiti Putra Malaysia, illustrates a heightened institutional interest in this field.